METODE DEMONSTRASI TERHADAP KETERAMPILAN DASAR PERMAINAN BULUTANGKIS PADA SISWA TUNARUNGU DI SMPLB - Dwi Suwida, Alfan (Jurnal Pendidikan Khusus, 2016)
ABSTRACT   Hearing impairment students had disturbance in speaking. The lack of comprehension in oral language caused their emotion depressed. The disturbance of the hearing impairment emotion development could be minimized through giving skill suitable with the talent and interest. One of the skills which could be given was badminton. The purpose of this research was to prove the influence of demonstration method toward badminton basic skill to hearing impairment students in SMPLB-B Karya Mulia Surabaya. This research used quantitative approach with pre-experimental kind and the research arrangement was one-group pretest-posttest design. The subject was hearing impairment children in SMPLB-B Karya Mulia Surabaya numbering 5 children. The data collection technique used test and observation. The data analysis technique used statistic non parametric with match pair test. Based on the result of data analysis in 1 side test there was significant influence whereas in 2 sides test there was not significant influence of demonstration method toward badminton basic skill to hearing impairment students in SMPLB-B Karya Mulia Surabaya.   Keywords: Demonstration method, badminton basic skill